Analisis Strategi Visual dan Tren TikTok dalam Meningkatan Brand Awareness UMKM: Tinjauan Pustaka Sistematis - I Gede Pasek Wiryatama; Kadek Adyatna Wedananta (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
Digital transformation has changed the marketing industry, enabling micro, small, and medium enterprises (MSMEs) to use platforms such as TikTok to expand their reach. With over one billion active users, especially among the younger generation, TikTok offers a short video format that supports interactive visual content to quickly build brand awareness. However, there are several challenges, such as understanding visual strategies and trends, which can be obstacles for MSMEs. Previous research shows that visual approaches are highly effective but lack structured synthesis. This study aims to identify dominant visual elements and TikTok trends that can increase brand awareness for MSMEs, while providing theoretical and practical guidelines for entrepreneurs, academics, and policymakers. The method used is a systematic literature review with a qualitative approach, selecting articles from sources such as Google Scholar and Garuda, focusing on keywords related to visual strategies and TikTok trends. The results show that visual elements such as authentic stories, trending music, and the use of filters can increase interaction, while trends such as hashtag challenges and collaborations with influencers can strengthen viral potential through algorithms. The main challenges faced are limited resources and digital literacy levels. Practical implications include training in digital skills and collaboration with influencers to maximize the use of TikTok, which will support innovation in MSME marketing strategies.